(untitled) (KIUT Publication, 2025)
This article provides a scientific and in-depth analysis of the opportunities and ways of broadly introducing green innovations into small business and private entrepreneurship. The study reveals the essence of the concept of green innovations and highlights their significance in enhancing the competitiveness of small business and entrepreneurial entities, as well as in ensuring environmentally sustainable development. The author develops specific mechanisms and recommendations aimed at increasing economic efficiency and reducing environmental risks through the implementation of green technologies. In addition, the article presents the advantages of applying green innovations based on international experience, identifies the main challenges in their implementation, and proposes measures to overcome them.